Digitization of Agribusiness Payments in Africa : Building a Ramp for Farmers’ Financial Inclusion and Participation in a Digital Economy - World Bank Group (World Bank, Washington, DC, 2020)
This report aims to present the rationale for digitization of agribusiness payments in Sub-Saharan Africa (SSA), assess the current status of digitization using demand and supply-side data, and identify key actions that can help accelerate digitization. The report draws on an analysis of financial-inclusion data from the Global Findex database, a survey administered to select agribusinesses active in SSA (henceforth referred to as the Africa Agribusiness Payments Survey, or AAPS), and case studies of select agribusinesses that responded to this survey. The Findex data analysis leverages questions in the survey that identify whether the respondent had received payment against the sale of an agricultural good; how the payment was received, in cash or through a digital means, defined to include an account at a bank or non-bank financial institution, mobile money account, or a card, and, if an account holder, whether the account was opened to receive an agricultural payment. The AAPS was administered to purposefully selected agribusinesses active in SSA, with either a regional or national scope. Some firms were added to the survey since they were known to have an active digitization program, but this was not a requirement for inclusion in the survey.